Técnicas del compostaje para la elaboración de biofermentos de origen sólido - Romero Barco, Ana Gabriel (2022)
This document deals with composting techniques for the production of bioferments of solid origin. The composting technique can be defined as a biotechnique where it is possible to exercise control over the biodegradation processes of organic matter. The product of this degradation is called Compost, which results from the aerobic degradation of material or waste of organic origin. The conclusions determine that the mineralization and recovery of nitrogen is higher in aerobic composting compared to anaerobic composting; the composition of urban solid waste for composting contained degradable material that included kitchen waste, market waste, leaves, twigs, grass, paper, clothing, cotton, wood, sawdust and other waste and composting techniques with static piles and soil pits to determine the best method of handling urban solid waste. Soil pit composting is the least efficient composting method compared to static pile composting.